A case report on cyclopentolate-induced psychosis - Kotturi, Dr. Sasanka; Kiran, Dr. P Sai (Indian Journal of Case Reports, 2024)
Cyclopentolate is a cycloplegic drug of choice for children that rarely causes central anticholinergic syndrome when it reaches systemic circulation. The lower body weight is one of the etiological factors. The manifestations could be behavioral and psychotic. We report a case of a 6-year-old child who developed acute psychosis following cyclopentolate instillation.